The Gender Inequality Issues Depicted in “The Queen’s Gambit (2020) Serial Movie by Scott Frank - Yumita Namirah; Retno Ramadhina; Lyla Nawakwulan (Journal Innovation In Education, 2025)
Gender discrimination refers to the unfair treatment of individuals based on their sex and often occurs in various aspects of social life, including the workplace, education, and media. The film *The Queen's Gambit* portrays the journey of a female chess player, Beth Harmon, who faces numerous challenges in a male-dominated world. This article explores the theme of gender discrimination depicted in the film and analyzes how the representation of Beth Harmon reflects the real-life experiences of women in traditionally male-dominated fields. Using a critical analysis approach, this study identifies and evaluates the different forms of discrimination faced by Beth, both structural and interpersonal, and their impact on character development and narrative. Findings indicate that while Beth Harmon manages to overcome gender barriers to achieve success, the film still reflects and highlights the systemic challenges faced by women in competitive fields. This article contributes to the understanding of gender dynamics in the context of popular media and offers insights into how gender representation in film can influence public perceptions and social norms.